FOREWORD: EDITORS’ INTRODUCTION - Pinto, Ângelo Parise; Monné, Marcela L.; Paulson, Dennis R.; Takiya, Daniela M.; Calor, Adolfo R.; Duarte, Marcelo; Salles, Frederico F.; Nihei, Silvio S. (Zootaxa, 2016)
Since its establishment ZOOTAXA has become not only a rapid journal for zoological systematics but also a respected forum for discussions of all taxonomic matters, and it has gradually attained a distinguished position among other zoological journals by its special issues. These collections of papers treat varied themes such as the Carl Linnaeus legacy (Zhang & Shear 2007, Minelli et al. 2008), cataloguing metazoan life (Zhang 2011, 2013), and promoting and discussing the future of taxonomic sciences, for example modification of the International Code of Zoological Nomenclature (ICZN 2008). For these reasons we offer this special issue to celebrate the fruitful career of the eminent Brazilian researcher Dr. Angelo Barbosa Monteiro Machado (“Professor Angelo” to his friends and colleagues).